1994
DOI: 10.1111/j.1476-5381.1994.tb14021.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial function in the isolated perfused mesentery and aortae of rats with streptozotocin‐induced diabetes: effect of treatment with the aldose reductase inhibitor, ponalrestat

Abstract: 1 Noradrenaline sensitivity and relaxation to acetylcholine were investigated in the isolated perfused mesentery and in aortic rings of control and streptozotocin (STZ)-induced (50 mg kg-') diabetic Charles River rats. 2 In addition, noradrenaline sensitivity and acetylcholine relaxation were similarly assessed in streptozotocin-induced diabetic rats treated from the time of onset of diabetes with the aldose reductase inhibitor, ponalrestat (100 mg kg-' day-'). 3 The untreated diabetic rats (2-10 weeks after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 58 publications
3
35
1
1
Order By: Relevance
“…Consequently, aldose reductase inhibitors were tested for their ability to improve endothelial dysfunction in experimental models of diabetes. Chronic oral treatment with structurally dissimilar aldose reductase inhibitors restored abnormal endothelium-dependent vasodilatation in all (Cameron & Cotter, 1992;Tesfamariam et al, 1993;Otter & Chess-Williams, 1994;Quilley et al, 1996) but one (Taylor et al, 1994b) study. The mechanisms responsible for the bene®cial e ects of aldose reductase inhibitors have not been elucidated, but several hypotheses have been formulated.…”
Section: Aetiology Of Endothelial Dysfunction In Diabetesmentioning
confidence: 95%
See 1 more Smart Citation
“…Consequently, aldose reductase inhibitors were tested for their ability to improve endothelial dysfunction in experimental models of diabetes. Chronic oral treatment with structurally dissimilar aldose reductase inhibitors restored abnormal endothelium-dependent vasodilatation in all (Cameron & Cotter, 1992;Tesfamariam et al, 1993;Otter & Chess-Williams, 1994;Quilley et al, 1996) but one (Taylor et al, 1994b) study. The mechanisms responsible for the bene®cial e ects of aldose reductase inhibitors have not been elucidated, but several hypotheses have been formulated.…”
Section: Aetiology Of Endothelial Dysfunction In Diabetesmentioning
confidence: 95%
“…Whereas di erences in diabetes model and in duration or severity of diabetes undoubtedly play a role in some of the discrepancies, the type of circulation, the size of the vessel and the conditions of study may be a much more important source of disparity. This has been typically illustrated by the presence of impaired endothelium-dependent vasodilatation in vivo in the mesenteric circulation or in the isolated perfused mesentery of diabetic rats, and by its absence in the isolated aorta of the same animals (Fortes et al, 1983;Taylor et al, 1994b). Similarly, bradykinin-mediated vasodilatation was depressed in the hindquarters vasculature, but was normal in the kidney and mesenterium of the same diabetic rats (Ki et al, 1991).…”
Section: Mechanisms Of Impaired Endothelium-dependent Vasodilatation mentioning
confidence: 97%
“…For example the contractile responses to the application of norepinephrine in vascular smooth muscle of experimentally diabetic animals have exhibited increase [1,4,9,29], decrease [10,21] or no change [7,28]. Therefore, we used newly developed experimental diabetic animals, alloxan-induced diabetes-susceptible (ALS) and resistant (ALR) mice, to study changes in the function of the vascular smooth muscle in diabetes mellitus.…”
Section: Induction Of Diabetesmentioning
confidence: 99%
“…High K + -induced and 5-HT-induced contractions were unchanged at all times, while the maximum contraction induced by NE and the sensitivity of contractile response to PGF 2α increased in preparations from longer period diabetic animals. Many investigators have reported in various experimental conditions that NE-induced contraction was increased [1,4,9,29], decreased [10,21] or unchanged [7,28] in diabetic animals. In our study NE-induced contraction was indicated to be potentiated when animals were in a diabetic state for longer than 2 months.…”
Section: Changes Due To Diabetesmentioning
confidence: 99%
“…Nas artérias mesentéricas in vivo e in vitro de animais diabéticos há redução da resposta induzida pela acetilcolina, enquanto que em aortas do mesmo animal essa resposta não se encontra alterada (FORTES et al, 1983b;TAYLOR et al, 1994). A duração do diabetes e o agonista usado também influenciam a resposta encontrada para agentes vasoconstritores e vasodilatadores.…”
Section: Palavras-chavesunclassified